Beyond the Classroom: Exploring English Fluency among Students in an Islamic Dormitory - Apink Safrina; M. Sofyan Adi Pranata (Surakarta English and Literature Journal, 2025)
This study seeks to analyze the informal strategies as well as practices that students at Islamic dormitory use to improve their English language skill outside of formal classroom settings. The research adopted a qualitative case study design involving five 11th-grade students residing in the Islamic dormitory. Data were collected through semi-structured interviews, direct observations of student interactions and speaking abilities, along with field notes and checklists to ensure data validity. Interviews and observations took place directly within the dormitory context, focusing on students' use of English in daily activities. Data analysis was conducted through data compression, structured presentation, and thorough conclusion drawing to interpret the qualitative findings. The results revealed a wide variation in students’ English proficiency, ranging from beginner to advanced levels, mainly influenced by the supportive dormitory environment fostering language fluency. Social interactions guided by tutors and senior students were identified as critical to accelerating practical language mastery outside the classroom. Furthermore, the research highlighted the importance of a supportive social environment and dormitory facilities in enhancing English language skills.